EXAMINING THE IMPERATIVE CLAUSES IN MANGGARAI - Salahuddin Salahuddin (Linguistik Indonesia, 2023)
This study aims to formulate case markings in imperative clauses in the Manggarai language. This study examines several formulas of imperative clause rules in previous research, which distinguished the use of gi and ga in positive imperative clauses, and neka and asi markers in negative imperative clauses. An intense interview was conducted with native speakers of the Kempo dialect and compared other examples used in previous studies to build a thorough conclusion. Some critical findings in this research are, firstly, the particles gi and ga are not an enclitic attached to the word they follow; secondly, the particles gi and ga are not specific markers for imperative clauses because they can also appear in other clause forms (e.g., declarative clauses); and thirdly, the words neka and asi in the negative imperative clauses of the Manggarai language can be used interchangeably and do not change the meaning. Thus, this study proves that there are no unique markers in the imperative clauses of the Manggarai language because the form varies relatively depending on the context with whom one is talking.